A comprehensive study on flow conditioner design working in a fi-fi monitor - Bilir, A. C.; Vardar, N.; Dogrul, A. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2023)
The fire-fighting monitor is a widely used equipment in several ship types to maintain the fire protection of ships, offshore platforms and coastal regions. In this study, a custom design flow conditioner was created and analyzed numerically in terms of different plate thicknesses to homogenize the flow properties in downstream of the flow conditioner. The numerical analyses were carried out by solving unsteady RANS equations. Different inlet pressures were tested for 200mm plate and the fi-fi monitor with three different plate configurations were analyzed in terms of streamlines, outlet pressure, mass flow and pressure drop. The numerical approach was validated for the 200mm thickness case. The numerical results were compared with the fi-fi monitor without flow conditioner. The results were discussed focusing on the flow region between the plate and the nozzle. The proper plate thickness was proposed by comparing the pressure drop coefficient and flow field parameter via streamlines.
Keywords: Science & Technology - Other Topics; Engineering